Pengaturan Hukum Terhadap Praktik Mediasi dalam Penyelesaian Sengketa - Yahya, Ahmad Septian (Universitas Proklamasi 45, 2025)
This study examines the effectiveness of legal regulations governing mediation in dispute resolution in Indonesia. Mediation as a non-litigation alternative is considered more efficient, affordable, and fair compared to litigation. Although regulated under Perma Number 1 of 2016 and several sectoral rules, its implementation faces challenges such as the limited quality of mediators, low public awareness, and the absence of a comprehensive legal framework. Using a normative legal approach, the research analyzes positive law and mediation practices both inside and outside the courts. Legal reform is needed, including the enactment of a Mediation Law, strengthening of mediator institutions, and online mediation regulation to meet modern demands.